Selection of clones robusta coffee with production potential in area of Zona da Mata-MG - Silva, Felipe Lopes da; Rezende, Juliana Costa de; Rodrigues, Fernanda Cupertino; Soles, Leila Caroline Toledo Cortez; Pereira, Vanessa Vitoriano; Malta, Marcelo Ribeiro (Coffee Science - ISSN 1984-3909, 2015)
The objective was to select superior clones as agronomic traits and caffeine content of the grains of Coffea canephora through appropriate biometric procedures, to compose a base population to growing in Minas Gerais state conditions. Thus, we evaluated 69 clones of C. canephora var. kouilouensis and 46 clones from C. canephora var. robusta, belonging to the Germplasm Bank of Epamig/UFV. The populations under study shows genetic variability. The selection of clones kouillou favor a gain above the overall average genotypic test 3%; 2.6%, 2.1%, 5.6%, 8.2% and 20.7%, respectively, for the characteristics vegetative vigor of plants, plant height average, diameter of plants average, diameter of the stems average, fruit size and yield. For robust clones the observed gains are: 0.7%; 4.1%; 2.8%; 3.6%, 1.5% and 21.6%, respectively, for the same characteristic measured above. Based on the desired agronomic traits, which presented lower levels of caffeine, the selected clones are 3013, 207, 303, 2029, 3036, 2014, 306 and 3015 for the kouillou group, and 101, 1028, 106 for the robust group, which will be used to compose a base population for the growing conditions in Minas Gerais.